Waterproof, low-temperature-resistant and soft reaction coating adhesive and preparation method thereof

By using polyurethane prepolymer, nanosiloxane, potato starch and other materials in the coating glue, the problem of waterproofing and unsatisfactory flexibility of traditional coating glue is solved, and a high-performance and environmentally friendly reactive coating glue is achieved.

CN119799247APending Publication Date: 2025-04-11HENAN JUYING NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411977746.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The waterproof and flexibility of traditional coating glue is not ideal, and it is not environmentally friendly, making it difficult to meet the needs of modern applications.

Method used

A waterproof, low-temperature soft reaction coating glue is prepared by using the ratio of polyurethane prepolymer, nanosiloxane, potato starch, modified epoxy resin, nanotitanium and crosslinking agent through high shear stirring, ultrasonic treatment and vacuum defoaming.

Benefits of technology

It achieves good elasticity and flexibility of coating glue, improves waterproofing and breathability, and enhances biodegradability and environmental friendliness, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799247A_ABST
    Figure CN119799247A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of coating adhesives, and particularly discloses a waterproof, low-temperature-resistant and soft reaction coating adhesive and a preparation method thereof.The waterproof, low-temperature-resistant and soft reaction coating adhesive is prepared from 30-50 wt% of polyurethane prepolymer, 25-50 wt% of nano siloxane, 10-50 wt% of potato starch, 15-50 wt% of modified epoxy resin, 5-50 wt% of nano titanium and 5-10 wt% of cross-linking agent; the polyurethane prepolymer comprises modified polyurethane and polyether, and the molar ratio of the modified polyurethane to the polyether is 3: 1; the polyurethane prepolymer is used as a base material of the coating adhesive, so that the coating is endowed with good elasticity and flexibility, the modified polyurethane can improve the water resistance and weather resistance of the coating, the polyether chain segment can improve the flexibility and low-temperature performance of the coating, and a compact hydrophobic layer is formed through the nanoscale siloxane, so that the coating has good water resistance and weather resistance. The potato starch is combined, so that the biodegradability and the environment friendliness of the coating are improved, meanwhile, the adhesive force and the strength of the coating are enhanced, and the coating has excellent flexibility and elasticity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of coating adhesives, and in particular relates to a waterproof, low-temperature-resistant and soft reaction coating adhesive and a preparation method thereof. Background Art

[0002] Coating adhesive refers to an adhesive that can be applied to the surface of a material to form a coating to achieve functions such as bonding, sealing, and protection. Coating adhesives are generally in liquid or paste form and are applied to the surface of a substrate through processes such as coating or spraying. After curing, a solid coating is formed. Reactive coating adhesives refer to adhesives that are cured through chemical reactions after coating to form a solid and durable coating material.

[0003] However, the traditional coating adhesives are not waterproof and flexible, and are not environmentally friendly enough, which makes them unsuitable for use. Summary of the invention

[0004] The purpose of the present invention is to provide a waterproof, low-temperature resistant and flexible reaction coating adhesive and a preparation method thereof, so as to solve the problem that the traditional coating adhesive has unsatisfactory waterproofness and flexibility.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A waterproof, low-temperature-resistant and soft reaction coating adhesive, comprising: 30-50wt% of polyurethane prepolymer, 25-50wt% of nano-siloxane, 10-50wt% of potato starch, 15-50wt% of modified epoxy resin, 5-50wt% of nano-titanium, and 5-10wt% of cross-linking agent;

[0007] The polyurethane prepolymer comprises modified polyurethane and polyether, and the molar ratio of the modified polyurethane to the polyether is 3:1.

[0008] Preferably, the cross-linking agent is one of hydrogen dioxide and isocyanate.

[0009] A method for preparing a waterproof, low-temperature resistant and soft reactive coating adhesive, the steps are as follows:

[0010] S1, introducing the polyurethane prepolymer and the modified epoxy resin into a high shear mixer, setting the high shear mixer to operate in a low speed mode, and mixing at a low speed for 10 to 25 minutes to obtain a mixed matrix;

[0011] S2, adding nano-siloxane, nano-titanium and potato starch into the mixed matrix, and transferring the mixed matrix into an ultrasonic cleaning machine for treatment to obtain a mixed solution;

[0012] S3, adding the mixed solution after ultrasonic treatment into the high shear mixer again, switching to high speed mode, and stirring and mixing at high speed for 25 to 30 minutes;

[0013] S4. Slowly add the crosslinking agent into the high shear mixer while stirring for 5 to 10 minutes to obtain a coarse material;

[0014] S5. The obtained coarse material is transferred to a vacuum degassing tank, the coarse material is degassed using the vacuum degassing tank, and the degassed coarse material is filtered using a 200-mesh sieve to obtain a coating adhesive.

[0015] Preferably, the stirring speed of the high shear mixer in step S1 is 100 to 300 rpm, and the stirring speed of the high shear mixer in step S2 is 400 to 600 rpm.

[0016] Preferably, heating is performed during the stirring process in step S1, and the heating temperature is 40 to 60 degrees Celsius.

[0017] Preferably, the ultrasonic cleaning agent in step S2 is used for an ultrasonic time of 30 to 60 minutes.

[0018] Preferably, in step S2, the potato starch is pre-cleaned before use, poured into a centrifuge for centrifugal dehydration after cleaning, then placed in a low-temperature vacuum dryer for low-temperature vacuum drying, and pulverized using a pulverizer.

[0019] Preferably, the temperature of the low-temperature vacuum dryer is 30 to 50 degrees Celsius, and the grinding fineness is 800 mesh.

[0020] Preferably, a thickener may be appropriately added in step S4, and the thickener is a mixture of hydroxyethyl cellulose and gelatin.

[0021] Preferably, the vacuum setting of the vacuum degassing tank in step S5 is 0.08 MPa, and the degassing time is 8 minutes.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The invention uses polyurethane prepolymer as the base material of the coating adhesive to give the coating good elasticity and flexibility, the modified polyurethane can improve the water resistance and weather resistance of the coating, the polyether segment can improve the flexibility and low-temperature performance of the coating, and the nano-scale siloxane forms a dense hydrophobic layer to improve the waterproof performance and air permeability of the coating. The potato starch is combined to improve the biodegradability and environmental friendliness of the coating, while enhancing the adhesion and strength of the coating. The invention has low cost and can reduce production costs, and the cross-linking agent can undergo cross-linking reactions with active groups such as hydroxyl groups and amino groups on the potato starch to enhance its binding property with the polymer substrate, and has excellent flexibility and elasticity. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0025] Figure 1 The figure is a flowchart of the method steps of the present invention. DETAILED DESCRIPTION

[0026] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings.

[0027] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0028] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0029] As attached Figure 1 As shown:

[0030] Embodiment 1: This embodiment provides a waterproof, low-temperature resistant and soft reaction coating adhesive, the composition ratio includes: 30-50wt% of polyurethane prepolymer, 25-50wt% of nano-siloxane, 10-50wt% of potato starch, 15-50wt% of modified epoxy resin, 5-50wt% of nano-titanium, and 5-10wt% of cross-linking agent;

[0031] The polyurethane prepolymer comprises modified polyurethane and polyether, and the molar ratio of the modified polyurethane to the polyether is 3:1.

[0032] Specifically, the cross-linking agent is hydrogen dioxide.

[0033] Polyurethane prepolymer is the base material of coating adhesive, which gives the coating good elasticity and flexibility. Modified polyurethane can improve the water resistance and weather resistance of the coating, and polyether chain segments can improve the flexibility and low-temperature performance of the coating.

[0034] Nano-scale siloxane has excellent hydrophobicity and air permeability, which can effectively improve the waterproof performance and air permeability of the coating. The nano-size enables it to be evenly dispersed in the coating to form a dense hydrophobic layer;

[0035] Potato starch, as a natural polymer material, can improve the biodegradability and environmental friendliness of the coating, has good bonding and film-forming properties, can enhance the adhesion and strength of the coating, and is low in cost, which can reduce production costs;

[0036] The modified epoxy resin has good adhesion, chemical corrosion resistance and mechanical strength. The modified epoxy resin can improve the compatibility with the polyurethane prepolymer, improve the comprehensive performance of the coating, and improve the hardness and wear resistance of the coating;

[0037] Nano-scale titanium dioxide has excellent ultraviolet shielding properties, can improve the weather resistance and anti-aging properties of the coating, has photocatalytic activity, and can give the coating a certain self-cleaning function;

[0038] The role of the cross-linking agent is to cross-link with the active groups on the polymer chain to form a three-dimensional network structure, thereby improving the mechanical strength, heat resistance and chemical corrosion resistance of the coating;

[0039] Hydrogen dioxide is used as a cross-linking agent, which will undergo a cross-linking reaction with active groups such as hydroxyl and carboxyl groups on the polymer chain. The hydrogen dioxide cross-linking reaction is mild, easy to control, and is conducive to forming a uniform network structure.

[0040] A method for preparing a waterproof, low-temperature resistant and soft reactive coating adhesive, the steps are as follows:

[0041] S1. Introducing the polyurethane prepolymer and the modified epoxy resin into a high shear mixer, setting the high shear mixer to operate in a low speed mode, and mixing at a low speed for 10 to 25 minutes to obtain a mixed matrix. By preparing a uniform mixed matrix, a good foundation is provided for the subsequent addition of nanomaterials and cross-linking agents;

[0042] S2, adding nano-siloxane, nano-titanium and potato starch to the mixed matrix, and transferring to an ultrasonic cleaning machine for treatment to obtain a mixed solution. Ultrasonic treatment can effectively prevent the agglomeration of nanomaterials and promote their uniform dispersion in the matrix;

[0043] S3, adding the mixed solution after ultrasonic treatment into the high shear mixer again, switching to high speed mode, and stirring and mixing at high speed for 25 to 30 minutes. High speed stirring can further improve the dispersion uniformity of each component and promote the interaction between the nanomaterial and the resin matrix;

[0044] S4. Slowly add the crosslinking agent into the high shear mixer while stirring for 5 to 10 minutes to obtain a coarse material. The crosslinking agent reacts with the polymer chain to form a three-dimensional network structure, which gives the coating excellent mechanical properties and chemical corrosion resistance.

[0045] S5. Transfer the obtained coarse material to a vacuum degassing tank, use the vacuum degassing tank to degas the coarse material, and use a 200-mesh sieve to filter the degassed coarse material to obtain a coating adhesive. Vacuum degassing can effectively remove bubbles in the system and avoid defects in the coating. Use a 200-mesh sieve to filter the degassed coarse material to remove possible impurities and undispersed particles to obtain a uniform coating adhesive.

[0046] Specifically, the stirring speed of the high shear mixer in step S1 is 100 to 300 rpm, and the stirring speed of the high shear mixer in step S2 is 400 to 600 rpm.

[0047] Specifically, in step S1, heating is performed during the stirring process, and the heating temperature is 40 to 60 degrees Celsius.

[0048] Specifically, the ultrasonic cleaning agent in step S2 is used for an ultrasonic time of 30 to 60 minutes.

[0049] Specifically, in step S2, the potato starch is pre-cleaned before use, poured into a centrifuge for centrifugal dehydration after cleaning, then placed in a low-temperature vacuum dryer for low-temperature vacuum drying, and crushed using a pulverizer. The potato starch is pre-cleaned, centrifugally dehydrated and low-temperature vacuum dried before use, and crushed to 800 meshes, which is beneficial to improving its dispersibility and stability in the system.

[0050] Specifically, the temperature of the low-temperature vacuum dryer is 30 to 50 degrees Celsius, and the pulverization fineness is 800 mesh.

[0051] Specifically, a thickener may be appropriately added in step S4. The thickener is a mixture of hydroxyethyl cellulose and gelatin, which increases the viscosity of the system and facilitates the cross-linking reaction.

[0052] Specifically, in step S5, the vacuum setting of the vacuum degassing tank is 0.08 MPa, and the degassing time is 8 minutes.

[0053] Embodiment 2: This embodiment provides a waterproof, low-temperature resistant and soft reaction coating adhesive, the composition ratio includes: 30-50wt% of polyurethane prepolymer, 25-50wt% of nano-siloxane, 10-50wt% of potato starch, 15-50wt% of modified epoxy resin, 5-50wt% of nano-titanium, and 5-10wt% of cross-linking agent;

[0054] The polyurethane prepolymer comprises modified polyurethane and polyether, and the molar ratio of the modified polyurethane to the polyether is 3:1.

[0055] Specifically, the cross-linking agent is isocyanate.

[0056] Polyurethane prepolymer is the base material of coating adhesive, which gives the coating good elasticity and flexibility. Modified polyurethane can improve the water resistance and weather resistance of the coating, and polyether chain segments can improve the flexibility and low-temperature performance of the coating.

[0057] Nano-scale siloxane has excellent hydrophobicity and air permeability, which can effectively improve the waterproof performance and air permeability of the coating. The nano-size enables it to be evenly dispersed in the coating to form a dense hydrophobic layer;

[0058] As a natural polymer material, potato starch can improve the biodegradability and environmental friendliness of the coating, has good bonding and film-forming properties, can enhance the adhesion and strength of the coating, and is low in cost, which can reduce production costs. In addition, potato starch has good biocompatibility and low cost, can improve the performance of the coating, and has good moisture absorption and moisture permeability.

[0059] The modified epoxy resin has good adhesion, chemical corrosion resistance and mechanical strength. The modified epoxy resin can improve the compatibility with the polyurethane prepolymer, improve the comprehensive performance of the coating, and improve the hardness and wear resistance of the coating;

[0060] Nano-scale titanium dioxide has excellent ultraviolet shielding properties, can improve the weather resistance and anti-aging properties of the coating, has photocatalytic activity, and can give the coating a certain self-cleaning function;

[0061] The role of the cross-linking agent is to cross-link with the active groups on the polymer chain to form a three-dimensional network structure, thereby improving the mechanical strength, heat resistance and chemical corrosion resistance of the coating;

[0062] Isocyanate is used as a cross-linking agent, which will undergo a cross-linking reaction with active groups such as hydroxyl and amino groups on potato starch to enhance its bonding with the polymer substrate. Isocyanate cross-linking reaction speed is fast and has high reactivity. The cross-linked coating has excellent flexibility and elasticity.

[0063] A method for preparing a waterproof, low-temperature resistant and soft reactive coating adhesive, the steps are as follows:

[0064] S1. Introducing the polyurethane prepolymer and the modified epoxy resin into a high shear mixer, setting the high shear mixer to operate in a low speed mode, and mixing at a low speed for 10 to 25 minutes to obtain a mixed matrix. By preparing a uniform mixed matrix, a good foundation is provided for the subsequent addition of nanomaterials and cross-linking agents;

[0065] S2, adding nano-siloxane, nano-titanium and potato starch to the mixed matrix, and transferring to an ultrasonic cleaning machine for treatment to obtain a mixed solution. Ultrasonic treatment can effectively prevent the agglomeration of nanomaterials and promote their uniform dispersion in the matrix;

[0066] S3, adding the mixed solution after ultrasonic treatment into the high shear mixer again, switching to high speed mode, and stirring and mixing at high speed for 25 to 30 minutes. High speed stirring can further improve the dispersion uniformity of each component and promote the interaction between the nanomaterial and the resin matrix;

[0067] S4. Slowly add the crosslinking agent into the high shear mixer while stirring for 5 to 10 minutes to obtain a coarse material. The crosslinking agent reacts with the polymer chain to form a three-dimensional network structure, which gives the coating excellent mechanical properties and chemical corrosion resistance.

[0068] S5. Transfer the obtained coarse material to a vacuum degassing tank, use the vacuum degassing tank to degas the coarse material, and use a 200-mesh sieve to filter the degassed coarse material to obtain a coating adhesive. Vacuum degassing can effectively remove bubbles in the system and avoid defects in the coating. Use a 200-mesh sieve to filter the degassed coarse material to remove possible impurities and undispersed particles to obtain a uniform coating adhesive.

[0069] Specifically, the stirring speed of the high shear mixer in step S1 is 100 to 300 rpm, and the stirring speed of the high shear mixer in step S2 is 400 to 600 rpm.

[0070] Specifically, in step S1, heating is performed during the stirring process, and the heating temperature is 40 to 60 degrees Celsius.

[0071] Specifically, the ultrasonic cleaning agent in step S2 is used for an ultrasonic time of 30 to 60 minutes.

[0072] Specifically, in step S2, the potato starch is pre-cleaned before use, poured into a centrifuge for centrifugal dehydration after cleaning, then placed in a low-temperature vacuum dryer for low-temperature vacuum drying, and crushed using a pulverizer. The potato starch is pre-cleaned, centrifugally dehydrated and low-temperature vacuum dried before use, and crushed to 800 meshes, which is beneficial to improving its dispersibility and stability in the system.

[0073] Specifically, the temperature of the low-temperature vacuum dryer is 30 to 50 degrees Celsius, and the pulverization fineness is 800 mesh.

[0074] Specifically, a thickener may be appropriately added in step S4. The thickener is a mixture of hydroxyethyl cellulose and gelatin, which increases the viscosity of the system and facilitates the cross-linking reaction.

[0075] Specifically, in step S5, the vacuum setting of the vacuum degassing tank is 0.08 MPa, and the degassing time is 8 minutes.

[0076] Importantly, it should be noted that the construction and arrangement of the present application shown in a plurality of different exemplary embodiments are only exemplary. Although only a few embodiments are described in detail in this disclosure, it should be readily understood by those who refer to this disclosure that many modifications are possible (e.g., the size, scale, structure, shape and proportion of various elements, and parameter values ​​(e.g., temperature, pressure, etc.), installation arrangement, use of materials, color, directional changes, etc.) without substantially departing from the novel teachings and advantages of the subject matter described in the application. For example, the element shown as integrally formed can be composed of multiple parts or elements, the position of the element can be inverted or otherwise changed, and the nature or number or position of the discrete element can be changed or changed. Therefore, all such modifications are intended to be included in the scope of the present invention. The order or sequence of any process or method steps can be changed or reordered according to alternative embodiments. In the claims, any "device plus function" clause is intended to cover the structure of performing the function described herein, and is not only structurally equivalent but also equivalent structure. Without departing from the scope of the present invention, other replacements, modifications, changes and omissions can be made in the design, operating conditions and arrangement of the exemplary embodiments. Therefore, the invention is not limited to a specific embodiment, but extends to numerous modifications still falling within the scope of the appended claims.

[0077] Additionally, in order to provide a concise description of exemplary embodiments, all features of an actual embodiment (ie, those features that are not relevant to the best mode presently contemplated for carrying out the invention or those that are not relevant to implementing the invention) may not be described.

[0078] It will be appreciated that in the development of any actual implementation, as in any engineering or design project, numerous implementation-specific decisions may be made. Such a development effort may be complex and time-consuming, but will be a routine task of design, fabrication, and production for those of ordinary skill having the benefit of this disclosure without undue experimentation.

[0079] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A waterproof, low temperature resistant and soft reaction coating adhesive, characterized in that: The composition ratio includes: 30-50wt% of polyurethane prepolymer, 25-50wt% of nano-siloxane, 10-50wt% of potato starch, 15-50wt% of modified epoxy resin, 5-50wt% of nano-titanium, and 5-10wt% of cross-linking agent; The polyurethane prepolymer comprises modified polyurethane and polyether, and the molar ratio of the modified polyurethane to the polyether is 3:

1.

2. The waterproof, low temperature resistant and soft reactive coating adhesive according to claim 1, characterized in that: The cross-linking agent is one of hydrogen dioxide and isocyanate.

3. A method for preparing a waterproof, low-temperature resistant and soft reaction coating adhesive, characterized in that: Here are the steps: S1, introducing the polyurethane prepolymer and the modified epoxy resin into a high shear mixer, setting the high shear mixer to operate in a low speed mode, and mixing at a low speed for 10 to 25 minutes to obtain a mixed matrix; S2, adding nano-siloxane, nano-titanium and potato starch into the mixed matrix, and transferring the mixed matrix into an ultrasonic cleaning machine for treatment to obtain a mixed solution; S3, adding the mixed solution after ultrasonic treatment into the high shear mixer again, switching to high speed mode, and stirring and mixing at high speed for 25 to 30 minutes; S4. Slowly add the crosslinking agent into the high shear mixer while stirring for 5 to 10 minutes to obtain a coarse material; S5. The obtained coarse material is transferred to a vacuum degassing tank, the coarse material is degassed using the vacuum degassing tank, and the degassed coarse material is filtered using a 200-mesh sieve to obtain a coating adhesive.

4. The method for preparing a waterproof, low-temperature-resistant and flexible reaction coating adhesive according to claim 3, characterized in that: The stirring speed of the high shear mixer in step S1 is 100 to 300 rpm, and the stirring speed of the high shear mixer in step S2 is 400 to 600 rpm.

5. The method for preparing a waterproof, low-temperature-resistant and flexible reaction coating adhesive according to claim 3, characterized in that: In the step S1, heating is performed during the stirring process, and the heating temperature is 40 to 60 degrees Celsius.

6. The method for preparing a waterproof, low-temperature-resistant and flexible reaction coating adhesive according to claim 3, characterized in that: The ultrasonic cleaning agent in step S2 has an ultrasonic cleaning time of 30 to 60 minutes.

7. The method for preparing a waterproof, low-temperature-resistant and flexible reactive coating adhesive according to claim 3, characterized in that: In step S2, the potato starch is pre-cleaned before use, poured into a centrifuge for centrifugal dehydration after cleaning, then placed in a low-temperature vacuum dryer for low-temperature vacuum drying, and pulverized using a pulverizer.

8. The method for preparing a waterproof, low-temperature-resistant and flexible reaction coating adhesive according to claim 7, characterized in that: The temperature of the low-temperature vacuum dryer is 30-50 degrees Celsius, and the pulverization fineness is 800 meshes.

9. The method for preparing a waterproof, low-temperature-resistant and flexible reaction coating adhesive according to claim 3, characterized in that: In the step S4, a thickener may be appropriately added, and the thickener is a mixture of hydroxyethyl cellulose and gelatin.

10. The method for preparing a waterproof, low-temperature-resistant and flexible reaction coating adhesive according to claim 3, characterized in that: The vacuum setting of the vacuum degassing tank in step S5 is 0.08 MPa, and the degassing time is 8 minutes.